Cytogenetic analyses of Pseudopimelodus mangurus (Teleostei: Siluriformes: Pseudopimelodidae) - Martinez, Emanuel Ricardo Monteiro [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (International Society of Cytology, 2004)
The cytogenetic analyses showed that Pseudopimelodns mangurus has a diploid number of 2n=54 chromosomes (6M, 26SM, 12ST and 10A), single Ag-NORs on the short arm of a middle-sized ST pair, identified as pair 19, and a very small amount of C-band positive segments in two chromosome pairs. The Ag-NORs are C-band positive. The staining of the chromosomes of P. mangurus with CMA 3 reveled the occurrence of bright signals corresponding to the Ag-NORs segments, to the C-band positive segments and also to some C-band negative segments. The occurrence of a diploid number of 2n=54 in all species of the family Pseudopimelodidae and its absence among representatives of Pimelodidae and Heptapteridae, two related families previously considered, reinforces the hypothesis that Pseudopimelodidae is a monophyletic group. © 2004 The Japan Mendel Society.
Keywords: Ag-NORs; C-band; Chromomycin A3; Chromosomes; Karyotype; Pimelodidae; Pseudopimelodidae; Pseudopimelodus; Siluriformes; Teleostei